Using Social Scientific Criteria to Evaluate Cultural Theories: Encoding/Decoding Evaluated - Evan L. Kropp (KOME: An International Journal of Pure Communication Inquiry)
This article transcends the issue of conflicting theoretical schools of thought to formulate a method of social scientific style theory evaluation for cultural studies. It is suggested that positivist social scientific models of theory critique can be used to assess cultural models of communication to determine if they should be classified as theories. A set of evaluation criteria is formulated as a guide and applied to Stuart Hall’s Encoding/Decoding to determine if it is a theory. Conclusions find the sharing of criteria between schools of thought is judicious, Encoding/Decoding fits the established criteria, and Encoding/Decoding should be referred to as a theory.